5 day weekend : freedom to make your life and work rich with purpose - Halik, Nik; Gunderson, Garrett B. (Bard Press, 2017)
Presents a strategy "to build multiple streams of income that don't require you to work 8 to 5 in a company where you have little control of your time and compensation. The core money parts--keep more money, make more money, and grow more money--focus on ways to tighten your finances, increase your income, and develop passive investment strategies. The goal is to build regular, independent cash flow until they match your standard of living"--Amazon.com.